COMPARISON OF E-COMMERCE CONCEPT REVIEWED FROM THE LAW OF BUSINESS COMPETITION BETWEEN INDONESIA AND CHINA - Julia Mia Audina (Domus Legalis Cogitatio, 2025)
The rapid development of digitalization has a significant impact on economic growth, especially trade through electronic systems. The positive impact felt by sellers and buyers makes the development of the digital market increasingly in demand by business actors. The more business actors involved in trading through electronic systems, the more business competition will occur in the market. Predatory pricing practices and monopolies were suspected to have occurred in Tiktok's shop social commerce, resulting in the issuance of Minister of Trade Regulation Number 31 of 2023. This then makes the author want to examine using comparative studies with the Chinese State regarding licensing arrangements, advertising and supervision on e-commerce. This research was conducted using normative legal research with a comparative approach that examines e-commerce regulations between Indonesia and China. The result of this study concludes that e-commerce regulations in China and Indonesia are almost similar in terms of e-commerce licensing system. Indonesia and China require business actors to register their business on e-commerce platforms and e-commerce platforms must provide a means for business actors to register on the e-commerce platform. Although the rules regarding e-commerce have similarities, there are differences that lie in the part of e-commerce supervision by the government. Supervision is to help improve the digital economy so that there is equity in rural and urban areas, so that digital economic equity can run well from urban to rural areas.